Mentoring and Diversity Tips for Students and Professionals for Developing and Maintaining a Diverse Scientific Community - Landefeld, Thomas; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
Mentoring has always been an important factor in life and particularly in academia. In fact, making choices about educational pursuits and subsequent careers without input from mentors can prove disastrous. Fortunately many individuals have "natural" mentors and for them these choices are greatly facilitated. Others are not privileged with natural mentors and as such often struggle with making these tough choices. Many times these individuals are from under served and disadvantaged backgrounds, where mentors are too few and far between. For them, deciding on which career path to take can be based not only on insufficient information but oft times inaccurate information. Although the tips in this monograph are designed for helping all individuals who are interested in pursuing the study of science and science careers, a special mentoring focus is on those students who have not experienced the advantages of the privileged class. Additionally, tips are included for those who are interested in effectively mentoring these individuals. How and why a person gets to that point of wanting to mentor is not as important as the fact that they have made that commitment and this monograph will help them do exactly that.
Making Decisions About Careers in Science -- Mentors and Mentoring -- Minorities in Science -- Precollege and College Preparation for Becoming a Scientist -- Graduate vs. Professional School -- The Application Process -- Faculty Advising and Mentoring -- Surviving in Professional Careers -- Wrap Up and Guidelines.
Keywords: Science (General).; Medicine; Life sciences; Science, general; Science, general; Life Sciences, general; Education (general).; Biomedicine general; Learning & Instruction